1992
DOI: 10.1128/jvi.66.9.5443-5452.1992
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific DNA binding activity of simian virus 40 large T antigen: evidence for the cooperation of two regions for full activity

Abstract: We generated a series of COOH-terminal truncated simian virus 40 large tumor (T) antigens by using oligonucleotide-directed site-specific mutagenesis. The mutant proteins [T(1-650) to T(1-516)] were expressed in insect cells infected with recombinant baculoviruses. T(1-623) and shorter proteins [T(1-621) to T(1-516)1 appeared to be structurally changed in a region between residues 269 and 522, as determined by increased sensitivities to trypsin digestion and by altered reactivities to several monoclonal antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 76 publications
3
15
0
Order By: Relevance
“…It is interesting that T-ag-bd 131-260 interacts very poorly with the non-origin-containing DNA control fragments. This observation is consistent with studies by Lin et al (42), who concluded that a second region of T-ag, extending between residues 269 and 522, defines a region that is important for nonspecific DNA binding. Since T-ag-bd 131-260 lacks this region, this molecule would be expected to interact poorly with non-origin-containing DNA.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…It is interesting that T-ag-bd 131-260 interacts very poorly with the non-origin-containing DNA control fragments. This observation is consistent with studies by Lin et al (42), who concluded that a second region of T-ag, extending between residues 269 and 522, defines a region that is important for nonspecific DNA binding. Since T-ag-bd 131-260 lacks this region, this molecule would be expected to interact poorly with non-origin-containing DNA.…”
supporting
confidence: 93%
“…The best-defined and most extensively studied domain of T-ag is the origin DNA-binding domain (T-ag-bd) (2,49,60,71,81), also termed the T-ag-obd (44). Currently, there is some uncertainty regarding the exact boundaries of the T-ag-bd; it has been mapped to amino acids 131 to 259 (2), 132 to 246 (49), and 147 to approximately 247 (42). Nevertheless, peptides from all three size classes are known to be sufficient for sequence-specific binding to the SV40 origin region (2,33,49,72).…”
mentioning
confidence: 99%
“…SV40 T‐ag purified from Sf‐9 cells infected with recombinant baculovirus has been described previously [21, 26, 27]. The physical characteristics of recombinant T‐ag produced by Sf‐9 cells are similar to those for T‐ag expressed in mammalian cell lines, including DNA and p53 binding.…”
Section: Resultsmentioning
confidence: 99%
“…Papillomavirus DNA replication shows very distinctive similarities to SV40 replication, and the structural similarities between the DBDs in these two proteins indicate that T‐ag and E1 are highly related (Luo et al ., 1996; Enemark et al ., 2000). It has been recognized that DNA‐binding activities other than those accounted for by the DBD may exist in SV40 T‐ag, but the nature and function of those activities, as well as their precise location, have been difficult to determine (Lin et al ., 1992). However, previous footprinting experiments with T‐ag generally are consistent with the manner of DNA binding that we propose for E1 (SenGupta and Borowiec, 1994).…”
Section: Discussionmentioning
confidence: 99%